Noncanonical Functions and Cellular Dynamics of the Mammalian Signal Recognition Particle Components - Faoro, Camilla; Ataide, Sandro F. (Frontiers in Molecular Biosciences, 2021)
The signal recognition particle (SRP) is a ribonucleoprotein complex fundamental for co-translational delivery of proteins to their proper membrane localization and secretory pathways. Literature of the past decades has suggested new roles for individual SRP components, 7SL RNA and proteins SRP9, SRP14, SRP19, SRP54, SRP68 and SRP72, outside the SRP cycle. These noncanonical functions interconnect SRP with a multitude of cellular and molecular pathways, including virus-host interactions, stress response, transcriptional regulation and modulation of apoptosis in autoimmune diseases. Uncovered novel properties of the SRP components present a new perspective for the mammalian SRP as a biological modulator of multiple cellular processes. As a consequence of these findings, SRP components have been correlated with a growing list of diseases, such as cancer progression, myopathies and bone marrow genetic diseases, suggesting a potential for development of SRP-target therapies of each individual component. For the first time, here we present the current knowledge on the SRP noncanonical functions and raise the need of a deeper understanding of the molecular interactions between SRP and accessory cellular components. We examine diseases associated with SRP components and discuss the development and feasibility of therapeutics targeting individual SRP noncanonical functions.